2014
DOI: 10.1371/journal.pone.0097289
|View full text |Cite
|
Sign up to set email alerts
|

The SNP rs1883832 in CD40 Gene and Risk of Atherosclerosis in Chinese Population: A Meta-Analysis

Abstract: BackgroundThe complications of atherosclerosis such as coronary and cerebrovascular disease, are the most prevalent causes of mortality and morbidity worldwide. A single nucleotide polymorphism (SNP) rs1883832 (-1C/T) in CD40 gene has been recently suggested to contribute to the susceptibility to atherosclerosis in Chinese population; however, previous genetic association studies yielded inconsistent results.MethodsA meta-analysis of eligible studies reporting the association between rs1883832 and atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…CD40 is considered to determine T cell responses to antigen presentation and B cells immunoglobulin isotype switching, which plays a key role in the inflammatory and prothrombotic processes by bonding with CD40 ligand (CD40L) in atherosclerosis [ 37 ]. Previous study provided evidence of association of CD40 rs1883832 with an overall increased risk of CHD in Chinese population [ 38 ]. In the current study, a similar result was drawn that CD40 rs1800686-A allele contributed to CHD risk.…”
Section: Resultsmentioning
confidence: 99%
“…CD40 is considered to determine T cell responses to antigen presentation and B cells immunoglobulin isotype switching, which plays a key role in the inflammatory and prothrombotic processes by bonding with CD40 ligand (CD40L) in atherosclerosis [ 37 ]. Previous study provided evidence of association of CD40 rs1883832 with an overall increased risk of CHD in Chinese population [ 38 ]. In the current study, a similar result was drawn that CD40 rs1800686-A allele contributed to CHD risk.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic studies have identified correlations between singlenucleotide polymorphism (SNP) in the CD40 gene and atherosclerotic risk, in particular the -1T>C SNP in the Kozak consensus sequence of the CD40 gene (rs1883832) [43][44][45][46][47]. A meta-analysis of 7 studies identified a significant correlation between rs1883832 and atherosclerotic CVD in Chinese populations [45]. Recently, Sultan et al extended these findings to the Caucasian population and also studied the functional consequences of this SNP in endothelial cells [43].…”
Section: Cd40 Single-nucleotide Polymorphisms and Human Atherosclerotmentioning
confidence: 99%
“…Studies showed that polymorphisms in CD40 may influence individuals' susceptibility to the development of cardiovascular events [ 18 , 26 ]. Studies had reported the relationship between rs1883832 at CD40 locus and acute coronary syndrome [ 27 , 28 ]. In this study, we selected two different tag SNPs (rs1535045 and rs4239702) at the CD40 locus to analyze the relationship between the two different tag SNPs and CAD in Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%